2006
DOI: 10.1016/j.ijantimicag.2005.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment and resistance of unselected uropathogens in the elderly

Abstract: A population-based study was conducted among women over the age of 70 years with complaints of uncomplicated urinary tract infections (UTIs). The positive predictive value of the nitrite test alone or in combination with the leukocyte esterase test ranged between 83% and 99%. The nitrofurantoin prescription rate decreased whereas fluoroquinolone and amoxicillin/clavulanic acid prescriptions increased with increasing age. The aetiology of infection was age-dependent. Escherichia coli was the most commonly isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…After E. coli the most frequently encountered agents in non-complicated USI in elderly patients aged 70 and above are Proteus and Klebsiella pneumonia, P. aeruginosa and E. faecalis are the most isolated in complicated USI [27,28]. The most frequently isolated agents in our cases were E. coli, Candida sp., Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 71%
“…After E. coli the most frequently encountered agents in non-complicated USI in elderly patients aged 70 and above are Proteus and Klebsiella pneumonia, P. aeruginosa and E. faecalis are the most isolated in complicated USI [27,28]. The most frequently isolated agents in our cases were E. coli, Candida sp., Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 71%
“…This is thought to account for the relatively low incidence of bacteriuria after single or intermittent catheterisation. An illuminating study by [15] into the mechanism of bacterial invasion of the urinary tract via devices showed that the intraluminal ascent of bacteria is faster (32 -48 h) than extraluminal ascent (72 -168 h). Colonisation of the luminal surface, particularly of urinary devices, has been shown in a number of studies [16] [17] [18].…”
Section: Pathogenesis Of Catheter-associated Biofilmmentioning
confidence: 99%
“…Several studies have reported increasing trends in resistance against trimethoprim-sulfamethoxazole (TMP -SMZ) [2,3] fluoroquinolones and other antibiotics, including ciprofloxacin [4,5]. To reduce the rate of morbidity, an early treatment of UTIs is mandatory, which relays on empirical therapies.…”
Section: Introductionmentioning
confidence: 99%